The aggregation behavior of Harmonia axyridis in its native range in northeast China - Wang, S.; Michaud, J. P.; Tan, X. L.; Zhang, F.; Guo, X. J. (My University, 2010)
Harmonia axyridis has become notorious as an urban pest in many of the regions where it has been introduced, despite its numerous contributions to the biological control of insects injurious to agriculture and horticulture. Aggregative behavior prior to overwintering leads to invasions of human habitations as beetles seek refuge from freezing temperatures. Here we describe the aggregation behavior of native H. axyridis populations of northeast China that breed in agricultural fields (mostly corn and rice) and shrub/forest habitats and then migrate through rural villages in autumn. More than 140,000 beetles were collected during direct observations in 16 villages in five townships in Jilin Province. Beetles aggregated on dwellings shortly after agricultural harvests, favoring white walls with southern exposures, the largest aggregations occurring in villages in mountainous townships at higher elevations. The sex ratio was consistently female-biased and succinic phenotypes were more than twice as abundant as melanic phenotypes in all locations. A special trap compared the relative attractiveness of different surface colors (white[ yellow = black[green[red = natural wood) and potential baits (corn pollen = honey[caramel = cocoa[milk = blank control). All aggregations disappeared abruptly just prior to the first frost, whereupon beetles were discovered sheltering in montane caves with southern aspects at higher elevations. Villagers reported substantial expenditures on pesticides in efforts to eliminate beetles from their homes every autumn. Invasion of human habitations appears to be an intrinsic tendency of native H. axyridis populations in China, which is the result of behavioral adaptations for cold-avoidance.
Citation: Wang, S., Michaud, J.P., Tan, X.L., Zhang, F., & Guo, X.J. (2011). The aggregation behavior of Harmonia axyridis in its native range in northeast China. BioControl, 56(2), 193-206. https://doi.org/10.1007/s10526-010-9325-7
Keywords: Aggregation; Attraction; Bait; Coleoptera; Coccinellidae; Overwintering